HAND SOLDERING PROCESS TRAINING MATERIAL USING ADDIE APPROACH TO SUPPORT E-LEARNING IMPLEMENTATION IN XYZ COMPANY - Afma, Vera Methalina; Arifin, Zaenal (SIGMA TEKNIKA, 2024)
Training is very important to increase the productivity of the company. Without the right training, worker will not understand and not know how to do right process. Worker with right process will be achieve good product. Sometimes, the problem of lack training is no proper training material availability for process. In this paper, author want to create training material for soldering process because soldering process is one of critical process, no proper soldering training material and support e-training as new implementation in XYZ company, and author is using ADDIE approach to create it. From ADDIE approach, author create 2 training phase and 2 types of assessment and training use multi – sensory learning which are visual, auditive, kinesthetic and tactile. In visual, using interactive video, participants watch the video, do the process as they see in the video, give the explanation, and they can ask the trainer if any question. Then worker will get training more about product especially for quality, output and ergonomic. After implementing it, workers is more understand and they can produce good product and right quantity, and trainer is more comfortable to give training for workers.